PENCEGAHAN DAN PENANGANAN BULLYING PADA SISWA USIA SEKOLAH DASAR - Indah Hari Utami; Rina Rahmi (Universitas Islam Negeri Sumatera Utara, 2025)
The aim of this research is to determine the prevention and handling of bullying behavior in elementary school age students at Al-Majidiyah Private Elementary School, Bagan Sinembah sub-district, Rokan Hilir district, Riau. This type of research is field research using qualitative descriptive methods with data collection techniques through interviews, observation and documentation. The steps to analyze the data are using the Miles and Huberman data analysis model, namely data reduction, data presentation, and drawing conclusions. From the research results it can be concluded that a) There are indications of mild bullying behavior occurring at Al-Majidiyah Private Elementary School, namely in the form of verbal bullying and light physical contact. This is caused by various factors that support bullying behavior, such as family environmental factors, school environment and TV media and gadgets. b) Efforts made by the school to prevent and handle bullying behavior are by holding bullying outreach in schools, establishing policies regarding bullying behavior, building awareness and a sense of empathy for all school members and reporting bullying acts to the National Commission on Child Protection.Key words: Prevention and treatment, bullying, elementary school students